2005
DOI: 10.1021/ja053242d
|View full text |Cite
|
Sign up to set email alerts
|

Multipole Plasmon Resonances of Submicron Silver Particles

Abstract: Single crystal, silver particles of 215 +/- 10 nm size were synthesized in solution using the hydrogen reduction method and were characterized by UV-visible extinction spectroscopy and electron microscopy. The extinction spectra reveal the presence of higher order multipoles of the plasmon resonance, such as quadrupole, octupole, and hexadecapole, in addition to the dipole. The formation of higher order multipoles was continuously monitored during the particles growth. Mie extinction calculations were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
162
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(180 citation statements)
references
References 24 publications
13
162
0
5
Order By: Relevance
“…To study the influence of the dielectric environment, we consider NPs of different morphologies embedded in a medium with a refraction index n = 1.47, such as dimethyl sulfoxide (DMSO) or silica glass, and then, we compare the spectra with those in vacuum. In the case of silver, many results indicate the presence of polyhedral NPs with well-defined facets and vertices, like icosahedra, and decahedra, as well as fcc related morphologies like cubes and truncated cubes [17,18,[32][33][34][35][36][37][38]. Figure 1 shows the different structural motifs studied here.…”
Section: Resultsmentioning
confidence: 99%
“…To study the influence of the dielectric environment, we consider NPs of different morphologies embedded in a medium with a refraction index n = 1.47, such as dimethyl sulfoxide (DMSO) or silica glass, and then, we compare the spectra with those in vacuum. In the case of silver, many results indicate the presence of polyhedral NPs with well-defined facets and vertices, like icosahedra, and decahedra, as well as fcc related morphologies like cubes and truncated cubes [17,18,[32][33][34][35][36][37][38]. Figure 1 shows the different structural motifs studied here.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 5, the UV/Vis spectra of the solution corresponding to the particles of 1 and 4 nm show the presence, in both cases, of the SPR at 392 and 434 nm, respectively. This significant shift must be a direct consequence of the different particle sizes [15] and/or their different dielectric surrounding media: the lower the Ag particle size, the less contact with the apoferritin takes place. In fact, particles of 1 nm exhibit a SPR (392 nm) that is typical for uncoated Ag nanoparticles, whereas that (434 nm) of the 4-nm sized particle is more characteristic of Ag particles surrounded with a high refractive index shell.…”
Section: Resultsmentioning
confidence: 99%
“…Calculations have shown that as silver nanoprisms get even larger, higher order multipole resonances should become visible [3,59] Higher order multipole resonances in nanorods are well documented [60][61][62] and have also been observed in silver nanospheres. [63] A closer look at some of the spectra for the samples of our largest nanoprisms show a shoulder on the in-plane quadrupole resonance at $465 nm (Fig. S2, SI).…”
Section: Optical Propertiesmentioning
confidence: 91%